Answer:
a)$5.25
b)$7.75
c)sorry i’m not sure
Step-by-step explanation:
(f+g)(x) is equivalent to f(x) + g(x)
So that would be (7x-3) + (x²-4x) = x² + 7x - 4x - 3 = x² + 3x - 3
Hope this helps.
Pemdas
parenthaseese
exponents
muliplication or division
addition r subtraction
so first is multiplication since non partnehatases and exonents
3 times 6=18
now we have
3-18+2
add
3-18=-15
now we have
-15+2=-13
answer is -17 because of order of operations (PEMDAS)
Answer:
-2
Step-by-step explanation:
When you fill it in you get 4(2)+3(-3)-1 then multiply and add